Construction of a well-being index for families in Envigado, Colombia - Hernández Calle, Jonathan Andrés; Palacio-Marín, Nora; Arbeláez, Andrea Patricia; Bedoya-Carvajal, Oscar Augusto (Revista Colombiana de Ciencias Sociales, 2026)
The family has been extensively studied as a key determinant of well-being, given the influence of social, political, and economic changes that affect it. Consequently, this study aimed to develop a well-being index for families in Envigado, Colombia. It employed a mixed-methods approach consisting of two phases. The initial qualitative phase involved data collection through four focus groups, while the subsequent quantitative phase entailed designing a questionnaire aligned with the dimensions of well-being identified in the first phase. The qualitative findings highlighted that well-being is intrinsically linked to the harmony of living and social protection, encompassing dimensions such as education, health, interactions, among others. Meanwhile, the quantitative analysis established a well-being model centered on the dimensions of health and social cohesion. Notably, the results indicated a high level of well-being among families in Envigado. In conclusion, this index contributes to public policies in this municipality of Colombia.